The role and place of mid-day supervisors in primary schools - McNichol, Steven (2022)
This study focused on a group of staff who undertake an occupational role in almost every primary school in the United Kingdom: mid-day supervisors. Despite mid-day supervisors being present in most primary schools for a proportion of each day, little is known about the functions of their role or about those who undertake it. No previous research has focused solely on this role within primary schools, nor included mid-day supervisors themselves as sole participants. This thesis therefore makes a contribution to knowledge by exploring the functions of the mid-day supervisors’ role, the place of this role within primary school communities and the experience of undertaking the role from the perspective of mid-day supervisors themselves. The study took place within three primary schools in the East Midlands. At each school, I worked alongside the mid-day supervisors, taking on the role myself, for fifteen consecutive days. During this participatory stage, I made field notes to record my own experience, informal observations and, most often, conversations between myself and the mid-day supervisors I worked alongside. This provided an insight into not only the experience of undertaking the role myself, but of the mid-day supervisors’ experience of doing so at the school. This data was supplemented by interviews with some mid-day supervisors at each school, allowing further exploration of their past and current experience undertaking the role. This study finds that the role of the mid-day supervisor within each school was either marginalised from or legitimised within the school community (Wenger, 1998) through organisational positioning, influences within the wider community and interactions with those undertaking different roles. The study draws on various theories of role (Linton, 1936; Newcomb, 1950; Dahrendorf, 1973; Biddle, 1986) to highlight the impact this had on the obligatory, optional and forbidden aspects of how the role was enacted and the functions that mid-day supervisors performed in each school. The experience of occupying the role of a primary-school mid-day supervisor was heavily influenced by factors that either minimised or contributed to role strain, such as role conflict, role ambiguity and role overload. Where these factors were minimal, the experience of being a mid-day supervisor was generally a positive one. Where these factors were significant, this led to a negative experience of being a mid-day supervisor for those who occupied the role and resulted in frustration and job dissatisfaction.